Spectrophotometric Determination of Total Iron in Rice and Maize Samples - Rajbhandari, Armila; Subedi, Tara (Scientific World, 2013)
Scientific World, Vol. 11, No. 11, July 2013, page 101-104 DOI: http://dx.doi.org/10.3126/sw.v11i11.8562